Análisis del impacto de la producción minera en la recaudación tributaria del Ecuador: un estudio econométrico para el periodo 2018 – 2023. - Pinzón Cabrera, Jhordan Alexander (2024)
Tax collection is vital for a state to generate revenue, which is necessary to finance services such as healthcare, housing, education, and security. It also allows governments to redistribute wealth to reduce economic inequalities. In recent years, the mining sector has experienced remarkable growth, becoming one of the main pillars of the national economy, therefore, it is important to analyze its tax structure. The objective of this research is to evaluate the contribution of mining production to tax collection in Ecuador. Its scope is descriptive since it characterizes both the Ecuadorian mining sector and its tax structure. In addition, the study has an explanatory approach and uses a multiple linear regression model to analyze the cause- effect relationship between mining sector tax collection and mining production. This study is longitudinal, using monthly data from the Central Bank of Ecuador and the Internal Revenue Service. The results show that the Ecuadorian mining sector is composed of four regimes: artisanal mining, small-scale mining, medium-scale mining, and large-scale mining. The main minerals extracted in Ecuador are gold and copper concentrate, and there are two mining projects in production: Fruta del Norte and Mirador, both located in the province of Zamora Chinchipe. Income tax is the highest tax collected in the Ecuadorian mining sector. The mining sector's tax system classifies taxes into general and sectoral taxes, including mining royalties, mining profits, and conservation patents. The relationship between the sector's tax collection and mining production is significantly positive, i.e., when mining production increases by 1%, tax collection increases by US$30,102.